Metastatic Urothelial Carcinoma Presenting as Rectal Linitis Plastica: A Rare Case Report - Christina Lee; Nader Awad; Stuart Kostalas (Gastro Hep Advances)
A 63-year-old male with history of cystoprostatectomy for bladder urothelial carcinoma presented with rectal pain, tenesmus, and altered bowel habits. Magnetic resonance imaging showed asymmetric rectal wall thickening with perirectal edema, while a positron emission tomography scan revealed increased metabolic activity in the midrectum. Digital examination demonstrated a firm, woody consistency of the rectal wall. Endoscopic examination of the rectum displayed subepithelial involvement with normal overlying mucosa. Endoscopic biopsies were nondiagnostic, but ultrasound-guided transperineal sampling confirmed metastatic high-grade urothelial cancer. The patient received palliative radiotherapy and pembrolizumab. This case illustrates rectal linitis plastica, characterized by carcinomatous infiltration of the deep rectal layers while preserving the mucosa, necessitating deep tissue sampling.